Directing Attention Externally Enhances Agility Performance: A Qualitative and Quantitative Analysis of the Efficacy of Using Verbal Instructions to Focus Attention - Porter, Jared; Nolan, Russell; Ostrowski, Erik; Wulf, Gabriele (Frontiers in Psychology, 2010)
The primary purpose of this study was to investigate if focusing attention externally produced faster movement times compared to instructions that focused attention internally or a control set of instructions that did not explicitly focus attention when performing an agility task. A second purpose of the study was to measure participants’ focus of attention during practice by use of a questionnaire. Participants (N = 20) completed 15 trials of an agility “L” run following instructions designed to induce an external (EXT), internal (INT) attentional focus or a control (CON) set of instructions inducing no specific focus of attention. Analysis revealed when participants followed the EXT instructions they had significantly faster movement times compared to when they followed the INT and CON set of instructions; consistent with previous research the INT and CON movement times were not significantly different from each other. Qualitative data showed when participants were in the external condition they focused externally 67% of the time. When they were in the internal condition they focused internally 76% of the time, and when they were in the control condition they did not use an internal or external focus of attention 77% of the time. Qualitative data also revealed participants in the EXT, INT, and CON conditions switched their focus of attention at a frequency of 27%, 35%, and 51% respectively.